Hawarirooz and defending the invasion of Ba'athist enemy in the second year of war - Yousof Bakhtiari; hammid hassanpoor; AHMAD MEHDI JAMALI (علوم و فنون نظامی, 2018)
The Islamic Republic of Iran's Army aviation, according to its capabilities in supporting fire, heliborn, reconnaissance and evacuating the injured personnel was ready from the beginning to the end of the war in offensive and defensive operations, including the military strategy of the Islamic Republic of Iran to expel the enemy and repel the enemy's invasion ofenemy played a more effective role in the second year of the imposed war. Therefore, it is necessary to examine the experiences and performance of this unit and its staff in the context of the above dimensions, and its role in defeating and repelling the enemy's aggression. The general purpose of this paper is to explain the army aviation's performance in the areas of fire support, heliborn the forces, aerial reconnaissance and evacuation of the injured in the second year of the war. The results showed that the Iranian army aviation in the area of fire support of offensive and defensive units in the southern operations and in the area of the heliborn forces and transportation of ammunition and logistics in the operational areas of the west and northwest as well as the evacuation of injured and martyrs in the south and northwest and Also, in the field of aerial reconnaissance in operational areas of the south and northwest of the country, and played the effective role in the victories of the second year of the imposed war. Key words: army aviation, IRIA, Disposal of Aggression, Second Year of War